Pengaruh Kualitas Pelayanan Akademik Terhadap Kepuasan Mahasiswa Merdeka Belajar Kampus Merdeka Di Fakultas Ilmu Sosial Dan Ilmu Politik Universitas Tadulako - Pancali, Ni Kadek Yuni; Rivai, Abdul; Erdiyansyah (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
The MBKM program provides opportunities for students to study outside their study programs for several semesters. However, the implementation of the program is still hampered by students who have difficulty accessing the website, establishing communication between lecturers and managers, confusion in the procedures for registering and do not understand the benefits of the MBKM program, the slow response in converting the value of courses, and lack of attention in the MBKM program service process. This study aims to determine the effect of the quality of academic services on student satisfaction participants in the MBKM program at FISIP UNTAD. This study uses a quantitative approach, with the theory of service quality from Zeititalm (1990) consisting of tangible, reliability, responsiveness, assurance, and emphaty. Data collection techniques are carried out through observation, questionnaires, and documentation with the type of primary and secondary data. Sampling techniques using probability sampling, and determining samples using proportional random sampling, and totaling 85 respondents (Untad FISIP students). Data analysis uses simple linear regression analysis. The results showed that the quality of academic services simultaneously had a significant effect on the satisfaction of students participating in the MBKM FISIP UNTAD. This is evidenced from the simultaneous test f count ≥ f table of 72,338 ≥ 3.11 and the results of a simple linear regression test obtained a significance value of 0,000 (<0.05). So it can be concluded that H0 is rejected and H1 is accepted. This means that the quality of academic services simultaneously has a significant effect on student satisfaction. The coefficient of determination (KD) of 46.6% shows that the quality of academic services contributes significantly to the satisfaction of students participating in the Merdeka Campus Learning program, with the remaining 53.4% is influenced by other variables that are not examined in this study.